Properties of an optogenetic model for olfactory stimulation - Genovese, Federica; Thews, Marion; Möhrlen, Frank; Frings, Stephan (The journal of physiology, 2016)
In olfactory research it is difficult to deliver stimuli with defined intensity and duration to olfactory sensory neurons.Expression of channelrhodopsin 2 (ChR2) in olfactory sensory neurons provides a...
Gesehen am 13.02.2017